Investigating nanostructured liquid crystalline particles as prospective ocular delivery vehicle for tobramycin sulfate: Ex vivo and in vivo studies - Shreya Kaul; Upendra Nagaich; Navneet Verma (Wolters Kluwer Medknow Publications, 2021)
Tobramycin remains the anchor drug for bacterial keratitis treatment and management; however, unlike other aminoglycosides, it does not pass through the gastrointestinal tract. The aim of the current investigation was to formulate tobramycin-loaded nanostructured liquid crystalline particles as an ophthalmic drug delivery system to ameliorate its preocular residence duration and ophthalmic bioavailability. Tobramycin cubosomes were fabricated by liquid-lipid monoolein, water, and poloxamer 407 as a stabilizer. Corneal penetration studies exhibited that the apparent permeation coefficient of tobramycin cubosomes was nearly 3.6-fold greater than marketed tobramycin eye drops. Ocular in vivo analysis performed in rabbits' eyes manifested that the intensity of bacterial keratitis was reduced on day 3, and on day 5, the manifestations were considerably mitigated with tobramycin cubosomes as compared to marked eye drops. Pharmacokinetic study of rabbit aqueous humor demonstrated that the area under curve and the peak concentration of optimized cubosomes were 3.1-fold and 3.3-fold, respectively, which was significantly higher than marketed eye drops. Moreover, histopathological studies illustrated the existence of normal ocular structures, thus indicating that there was no damage to the corneal epithelium or stromal layer. Consequently, the results acquired demonstrated that tobramycin-loaded cubosomal formulation could be a propitious lipid-based nanodelivery system that would enhance retention time and corneal permeability contrast to commercial eye drops.